Anatomic and Functional Varieties of Labial Frenum in Children During the Mixed Dentition Period - Farida S. Ayupova; Tatyana V. Gayvoronskaya; Sergey N. Alekseenko (Кубанский научный медицинский вестник, 2019)
Aim. To study the anatomical and functional varieties of labial frenum and their prevalence in children aged 6–11 years in the territories of the Krasnodar Krai.Materials and methods. We have studied the prevalence of varieties of labial frenum anomalies in 120 children at the initial and fi nal periods of mixed dentition. A preventive examination of 60 children (1st observation group) and 60 children receiving orthodontic treatment (2nd observation group) at the children’s dental department of the Dental Clinic of the Kuban State Medical University was carried out. The criteria for inclusion in the observation groups were somatically healthy children, living in the city of Krasnodar, and the cities and areas of the Krasnodar Krai. Statistical analysis was performed using the Statistica 6.0 (StatSoft Inc., USA) software. Qualitative data were described using absolute values and percentages. To identify differences in the sign occurrence frequency between the groups under consideration, Fisher’s exact test was used due to the fact that the expected number of observations in the cells of the four-fi eld table was less than fi ve. The obtained value of the exact Fisher’s test p < 0.05 testifi ed to the absence of statistically signifi cant differences.Results. The prevalence of labial frenum anomalies reached 15% according to routine examination (1st observation group) and 20% — in children with dentoalveolar anomalies who applied for orthodontic treatment (2 observation group). No statistically signifi cant differences were observed between the groups of girls and boys by the prevalence of varieties of labial frenum anomalies (p > 0.05). In the 2nd observation group, labial frenum anomalies were detected 2 or more times more often (p < 0.05) in children living in cities (44.44%) and in the regions of the Krasnodar Krai, than in children living in the city of Krasnodar (21.43%).Conclusions. Anatomical and functional classifi cation refl ects the main varieties of the labial frenum and allows the indications for surgical intervention to be clarifi ed. An alteration trend of the attachment location of labial frenum to the gingiva was found due to the physiological increase in the dentoalveolar height in the jaw anterior parts during the eruption period of permanent teeth and the formation of their roots. In this regard, it is advisable to plan surgical intervention in the period of late mixed dentition taking into account the anatomical and functional variety of the labial frenum.